Bentuk Hegemoni dalam Novel Bidadari Bermata Bening Karya Habiburrahman el Shirazy - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
This research is based on the view that the characters in the novel have characters, roles and powers. The power of the figures shifts according to their respective roles and contexts. The research objective of the novel Bidadari Bermata bening (BBB) is to reveal the forms of character hegemony. This research enters the realm of sociology of literature with the Gramsci hegemony approach. The research method of the novel BBB is descriptive qualitative. The primary data of this research are in the form of words, sentences, paragraphs contained in the novel BBB. . The primary data of this research are in the form of words, sentences, paragraphs contained in the novel BBB. Secondary data or sources are in the form of a set of knowledge to explain the forms of hegemony. The research data were analyzed and interpreted based on the hegemony approach. The results showed, the form of hegemony in BBB, namely, kiai's son and servant strong. Kia;s son played Gus Afif and Ayna as servant strong. Gus Afif as kiai’s son handsome, and kind-hearted capable captivate Ayna. Likewise Ayna, as servant strong, capable melting heart Gus Afif. The hegemony of the two figures went well and peacefully, not coercion. The two characters are married and happy.